1989
DOI: 10.1002/em.2850130103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analyses of in vivo hprt mutant T cells from atomic bomb survivors

Abstract: In vivo-derived hprt-deficient mutant T cells isolated from three nonirradiated controls and two atomic bomb survivors were studied by Southern blot analysis to investigate the molecular spectra of the mutations. Mutant frequencies for the three controls were 1.8, 2.3, and 7.3 x 10(-6), and those for the two survivors (who had received radiation doses of 2.46 and 2.15 Gy, based upon the revised atomic bomb shielded kerma estimates) were 9.3 and 14.4 x 10(-6), respectively. Fourteen (13%) of 105 mutant T-cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…One HD patient underwent a significant clonal expansion, which greatly affected the MF. This also has been observed previously in two other studies (40,41). Therefore, we believe it is likely that the treatments induced persistently elevated mutation frequencies in only a subset of patients.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…One HD patient underwent a significant clonal expansion, which greatly affected the MF. This also has been observed previously in two other studies (40,41). Therefore, we believe it is likely that the treatments induced persistently elevated mutation frequencies in only a subset of patients.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, a study on atomic bomb survivors showed that when the clonal mutants are enumerated and the number of actual independent mutational events determined, those with elevated MFs had normal mutation frequencies when compared to controls (41). Thus, it is possible that all patients have a similar level of mutagenic damage induced in the hprt gene, but that the damage is visible as hprt mutants in only a subset, based on the probability of a particular T-cell responding to an antigenic stimulus later.…”
Section: Hd Patients Treated With Chemotherapymentioning
confidence: 99%
“…Each of these assays can detect, quantitate, and partially characterize somatic mutation and segregation events that have occurred in vivo during the development of lymphocytes or erythrocytes. Both have proven to be useful biodosimeters of mutagenesis in animals and adult humans [Hakoda et al, 1989;Albertini et al, 1990;Thilly, 1990;Grant and Jensen, 19931.…”
Section: Introductionmentioning
confidence: 99%
“…Some proportion even of those chromosomal aberrations which would be expected to be unstable persist with time (Bender and Gooch 1963 ). Using the same assay as our laboratory, Hakoda et al (1989) found that atomic bomb survivors had a significantly higher mutant frequency than controls 43 y after the event. Since radiotherapy technicians are not exposed to radiation in discrete doses but rather continuously, we could not examine persistence of mutants after cessation of exposure.…”
Section: Duration Of Rise In Cloning Eficiency and Mutant Frequencymentioning
confidence: 84%